2006
DOI: 10.1007/s11243-006-0093-2
|View full text |Cite
|
Sign up to set email alerts
|

Host (nanocavity of zeolite Y)/guest (Co(II), Ni(II) and Cu(II) complexes of unsaturated 16-membered octaaza; 3,4,11,12-tetramethyl-1,2,5,6,9,10,13,14-octaazacyclohexadecane; Me4[16]aneN8 nanocomposite materials (HGNM): template synthesis, characterization and catalytic oxidation of benzyl alcohol

Abstract: Nanocavity zeolite-Y (host) encapsulated Co(II), Ni(II) and Cu(II) complexes of unsaturated 3,4,11,2,5,6,9,10,13,aneN 8 '; macrocycle (guest) were synthesized and characterized by chemical analyses, s.e.m., x.r.d., u.v.-vis., d.r.s., surface area, pore volume, conductometric, magnetic measurements and i.r. spectroscopy with a view to confirming the encapsulation of complexes and to arrive at the composition, structure and geometry of encapsulated complexes. The characterization data show the absence of extrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…From the standpoint of environmental issues, the development of green chemistry procedures and environmentally friendly technologies are crucial to achieve sustainable growth. The immobilization of transition-metal complexes in zeolite has attracted much interest for the development of catalysts that combine the advantages of homogeneous and heterogeneous catalysis. We previously reported that iron–bipyridine complexes encapsulated into Na-Y zeolite ([Fe­(bpy) 3 ] 2+ @Y) possess high catalytic activity for the oxidation of cyclohexene and benzene using hydrogen peroxide to form their corresponding alcohols with high selectivity . Furthermore, the maximum value of catalytic activity for the oxidation of benzene with H 2 O 2 was achieved when the volume ratio of solvents (CH 3 CN and H 2 O) was equal (1:1) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the standpoint of environmental issues, the development of green chemistry procedures and environmentally friendly technologies are crucial to achieve sustainable growth. The immobilization of transition-metal complexes in zeolite has attracted much interest for the development of catalysts that combine the advantages of homogeneous and heterogeneous catalysis. We previously reported that iron–bipyridine complexes encapsulated into Na-Y zeolite ([Fe­(bpy) 3 ] 2+ @Y) possess high catalytic activity for the oxidation of cyclohexene and benzene using hydrogen peroxide to form their corresponding alcohols with high selectivity . Furthermore, the maximum value of catalytic activity for the oxidation of benzene with H 2 O 2 was achieved when the volume ratio of solvents (CH 3 CN and H 2 O) was equal (1:1) .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the maximum value of catalytic activity for the oxidation of benzene with H 2 O 2 was achieved when the volume ratio of solvents (CH 3 CN and H 2 O) was equal (1:1) . To date, many researchers have reported the immobilization of copper complexes in zeolite and their catalytic activity for the oxidation of sulfides, benzenes, alcohols, and other substrates using H 2 O 2 . However, little is known about their reactivity and reaction mechanism.…”
Section: Introductionmentioning
confidence: 99%